Tipu Daya Perempuan dalam Al-Qur’an Interpretasi Ma’na Cum Maghza Q.S Yusuf Ayat 28 - Saputra, Ramadona; Putri, Amelia; Fahruli, Sehilana (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Interpretations that associate deceit with women often oversimplify a more complex issue and reinforce harmful negative stereotypes about gender. Surah Yusuf, verse 28 recounts the slander faced by Prophet Yusuf and highlights his integrity and patience, without attributing deceit as an exclusive trait of women. This study is a descriptive-analytical literature review employing the Ma’na-cum-maghza hermeneutic approach, involving three phases of analysis: al- Ma’na at-Tarikhi (historical meaning), al-Maghza at-Tarikhi (historical phenomenal significance), and al-Ma’na al- Mutaharrik (dynamic phenomenal significance). The research findings indicate that the phrase "inna kaida kunna ‘adzim" in Surah Yusuf, verse 28 specifically refers to the false accusation made by Zulaikha against Yusuf, rather than an inherent trait of women. The three main messages identified are: (1) the importance of truth in judgment, showing that assessments should be based on evidence, not prejudice; (2) the necessity of upholding justice and integrity in addressing accusations; and (3) vigilance against false or manipulative claims. These messages are connected to contemporary contexts in al-Maghza al-Mutaharrik, emphasizing their relevance in evaluating reprehensible actions as individual responsibilities regardless of gender.